Paleoenvironmental dynamics in South Amazonia, Brazil, during the last 35, 000 years inferred from pollen and geochemical records of Lago do Saci. (1st October 2017) - Fontes, D.; Cordeiro, R.C.; Martins, G.S.; Behling, H.; Turcq, B.; Sifeddine, A.; Seoane, J.C.S.; Moreira, L.S.; Rodrigues, R.A.
Abstract: Paleoenvironmental changes for the last 35, 000 years were reconstructed from palynological, sedimentological and organic geochemical evidence from a well-dated sediment core from Lago do Saci (South Amazonia). Dry climatic conditions occurred between 35, 000 and 18, 200 cal yr BP as recorded by high frequencies of open savanna taxa and low lake level indicated by Sagittaria and low Total Organic Carbon content. Cold temperatures are indicated by the presence of Podocarpus and Ilex . A sedimentation hiatus observed between 18, 200 and 9200 cal yr BP was likely related to dry conditions. The beginning of the Holocene was marked by rainforest expansion and an increase in carbon content that represented high lake levels and warmer and wetter climate conditions. Between 7500 and 5000 cal yr BP, the expansion of open savanna, seasonal forest elements and abundant black carbon suggests a dry phase. After 5000 cal yr BP, rainforest expansion and higher lake levels indicate a return to wetter conditions. A reduction of flooding taxa ( Celtis and Mauritia ) between 1800 and 1300 cal yr BP, high lake level conditions and maintenance of a forest physiognomy, suggests a decrease of regional precipitation and subsequent reduction of the flooded areas in a still humid climate regime. Highlights: We analyze the late Pleistocene/Holocene environmental history of Saci Lake, Southern Amazonia. The Late Pleistocene was characterized by a cold and dry climate. The Holocene presents dry phase during mid-Holocene with increase humidity until late Holocene. Amazon palaeohydrological changes were analyzed associated with vegetational changes.